Preserving Traditional Islamic Thought and Practice: The Codified SūrahYāsīn and Taḥlīl Texts in Indonesia - Rohman Rohman (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2018)
Abstract This paper tries to construct the role of the codified SūrahYāsīn and Taḥlīl texts in Indonesia.The present paper also attempts to investigate the sequential aspects of the transmission of sūrahYāsīn from the single sūrah until it is compiled with taḥlīl texts and become widely used among traditionalist Muslims in Indonesia. The paper provides the faḍā’il al-a‘māl based on some muslim scholars. Some important questions will be dealt here, namely: why does sūrah Yāsīn has a special position? How was sūrahYāsīn and taḥlīl texts compiled in Indonesia? In this paper, I argue that the sūrahYāsīn compiled with taḥlīl texts is sort of textual forms which preserve the traditional Islamic thought and practices in Indonesia.